Students’ Perception on the Application of Merdeka Curriculum - Akrimah Nur Hulu (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aimes to find out the perceptions of Senior high school students and their reasons for applying Merdeka Curriculum in English subjects. In completing this qualitative research, the researcher adopted a phenomenological case study approach. Data was collected by distributing questioners to respondents and conducting in-depth interviews with selected students. The data was found by researchers were processed using thematic analysis techniques. This research involved senior high school students from 5 different schools in Medan, North Sumatra, totaling 38 students as respondents. From this study, researchers found five perceptions related to the application of the Merdeka Curriculum in English language subjects, namely a. Merdeka Curriculum provides freedom in learning; b. students are more active and creative, c. concise and simple material; d. energy consumption that is quickly drained or tiring; and e. Merdeka Curriculum is better than Curriculum 2013. In addition, five reasons were found from the students' perceptions, namely a. freedom to choose appropriate learning methods and strategies; b. students do a lot of activities in learning; c. the material in English books is more on points with minimal explanation; d. the assignments given are many and concurrent; and e. The Merdeka Curriculum is more student-centered than the 2013 Curriculum. Furthermore, a detailed explanation related to this will be described in detail in this study.